Case Report: Adult Still’s Disease in an Alemtuzumab-Treated Multiple Sclerosis Patient - Krämer, Julia; Krömer-Olbrisch, Tanja; Lakomek, Heinz-Jürgen; Schellinger, Peter D.; Foell, Dirk; Meuth, Sven G.; Straeten, Vera (Frontiers in Immunology, 2020)
Background: Autoimmune adverse events are the most relevant risks of alemtuzumab therapy. We present a patient with relapsing-remitting multiple sclerosis, who developed adult-onset Still’s disease (AOSD) following alemtuzumab treatment. Case presentation: The patient suffered from sore throat, swallowing difficulties, high spiking quotidian fever, generalized skin rash, arthritis, and myalgia two months after the second course of alemtuzumab. Laboratory tests revealed elevated acute-phase reactants, anemia, neutrophilic leukocytosis, and thrombocytosis. Serum calprotectin, interleukin-2 and interleukin-6 levels were strongly increased. Autoimmune, rheumatic, neoplastic, infectious, and granulomatous disorders were excluded. The NLRP1 and NLRP3 gene test, which was performed under the presumption of a cryopyrin-associated autoinflammatory syndrome, was negative. Based on the Yamaguchi and Fautrel criteria, and supported by the histological findings from a skin biopsy of the rash, the diagnosis of AOSD was established. Therapy with the anti-IL-1 agent (anakinra) led to a significant improvement of symptoms and blood parameters. However, anakinra had to be converted to rituximab due to generalised drug eruption. Following therapy with rituximab, the patient has fully recovered. Conclusion: The current case highlights AOSD as another rare and potentially life-threatening secondary autoinflammatory/autoimmune event following alemtuzumab treatment.